Mengelola Konflik Guru-guru melalui Pendekatan Kecerdasan Emosional - Fientje J.A. Oentoe (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
Conflicts may occur among individuals, groups, and organiza-tions. From managerial point of view, the existence of conflicts may have influence on the individual performance. In an organization, there might be substantive and emotional conflicts. The quality of a leader may therefore be indicated by his or her ability in managing such conflicts in order to create a more condusive climate in the working environment. It is suggested that the leader employ an emotional intelligence approach.